Rotor sleeve based on thermoplastic composite material

By using thermoplastic composite materials to prepare the rotor sleeve, the problems of complex preparation process and difficult recycling in the prior art are solved, and the effects of high strength, low eddy current loss and good heat resistance are achieved.

CN119452547APending Publication Date: 2025-02-14SOLVAY SPECIALTY POLYMERS USA LLC
View PDF 13 Cites 0 Cited by

Patent Information

Application Number
CN202380049715.3
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Priority Date
2022-10-08
Filing Date
2023-06-27
Publication Date
2025-02-14

AI Technical Summary

Technical Problem

The prior art is long and complicated in preparing sleeves based on thermoset composites surrounding the rotor, and it is difficult to achieve full or partial recycling, while the sleeves are difficult to meet the requirements of high strength and low eddy current losses at low thickness.

Method used

The rotor sleeve is prepared using thermoplastic composite material (TPC), which consists of polymer matrix and continuous fibers. The sleeve is prepared by pressure assembly or direct winding, and the strip is melted and consolidated by local heating by heat source.

Benefits of technology

The rapid preparation of the sleeve is achieved, with high strength, low eddy current loss and good heat resistance, and with potential full or partial recycling capabilities.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005208018960000041
    Figure BDA0005208018960000041
  • Figure BDA0005208018960000111
    Figure BDA0005208018960000111
  • Figure BDA0005208018960000121
    Figure BDA0005208018960000121
Patent Text Reader

Abstract

The invention relates to a rotor sleeve made of or comprising a thermoplastic composite material (TPC), the thermoplastic composite material (TPC) comprising or consisting of: (1) a polymer matrix (P); and (2) continuous fibers; wherein the polymer matrix (P) comprises or consists of: at least one thermoplastic polymer having a Tg higher than 90 DEG C and selected from the group consisting of a polyaryletherketone (PAEK), a polyphthalamide (PPA), a polyamide-imide (PAI), a polyphenylene sulfide (PPS) and a blend of two or more of said polymers; optionally at least one plastic additive; and wherein the continuous fibers are selected from the group consisting of: continuous carbon fibers (CF), and continuous glass fibers (GF).
Need to check novelty before this filing date? Find Prior Art

Description

[0001] This application claims priority to European Patent Application No. 22200446.7 filed on June 16, 2022, the contents of which are incorporated herein by reference in their entirety for all purposes. If there are any inconsistencies between the two applications that would affect the clarity of terminology or expression, reference should be made solely to the present application. [Technical field]

[0002] The invention relates to a rotor sleeve based on a thermoplastic composite material and to an electric machine or a rotor comprising such a rotor sleeve.

[0003] [Background technology and technical problems to be solved]

[0004] In recent years, there has been a marked increase in the trend towards designing and building fuel-efficient, low-emission or zero-emission on-road and off-road vehicles, with significant emphasis on the development of hybrid and all-electric vehicles. This, in turn, has led to a greater emphasis on electric motors, either as the sole propulsion source (e.g., all-electric vehicles) or as an auxiliary propulsion source in a combined propulsion system (e.g., hybrid or dual-motor vehicles).

[0005] In such applications, the motor can use an AC or DC permanent magnet motor design or an AC induction motor design. Regardless of the type of motor, the motor is usually designed for a specific application in order to achieve the desired efficiency, torque density or high-speed power with an acceptable motor size and weight. It is generally believed that increasing the rotational speed of the motor is one of the most attractive ways to improve the power density, thereby increasing the efficiency and thus increasing the range of the electric vehicle without increasing the size, cost and mass of the battery pack. By increasing the speed of the rotor, the parts of the rotating rotor may be exposed to great centripetal forces. If the parts are not properly held in place, they may even be slightly lifted from the rotor, which may cause motor failure. A known solution to this challenge is solved by using a rotor sleeve around the rotor. The rotor sleeve is a component arranged around the rotor. Its function is to mechanically hold the parts of the rotor, and more specifically the permanent magnets and ensure the integrity of the rotor, which is independent of the operating conditions, i.e., the rotational speed, temperature (which can vary from -40°C to +150°C), humidity, and the presence of fluids. The sleeve can be made of metal or composite materials. The most commonly used composite materials are those based on thermosetting matrices. WO2020 / 188006 (Safran) discloses a fiber-reinforced composite sleeve in a generator. WO2021 / 225902 (Tesla) discloses a rotor wrapped with a wound fiber sleeve.

[0006] US2022 / 278584 (D1) discloses a rotor sleeve for a rotor of an electric machine, which defines an axis of rotation and comprises: a plurality of carbon fiber reinforced polymer layers, each layer comprising fibers oriented substantially at 90° relative to the axis of rotation; at least one fiber layer with a lower elastic modulus provided between the carbon fiber reinforced polymer layers, wherein these fibers with a lower elastic modulus are oriented between 50° and 75° relative to the axis of rotation (X).

[0007] US 5,275,883 (D2) discloses a flexible composite material comprising a sheath surrounding a core consisting essentially of continuous fibers, the fibers being coated with a mixture of polymer powders that are transformable by temperature increase to form a connection with the fibers and the sheath. WO 2021 / 259757 (D3) discloses a method for preparing a carbon fiber reinforced poly(aryletherketone) composition. WO 2022152653 (D4) discloses a component comprising a PEEK-PEoEK film. These documents D2-D4 are not related to the rotor sleeve and do not disclose the rotor sleeve.

[0008] The production of a sleeve based on thermosetting composite materials around a rotor requires a specific, time-consuming and in some cases dirty (i.e. wet winding) process. Therefore, there is a need for a rotor sleeve that can be produced more easily. Furthermore, due to the increasing importance of the circular economy today, there is also a need for a rotor sleeve that can be fully or partially recycled.

[0009] The rotor sleeve needs to have the right combination of properties (even at low thickness), such as low eddy current losses, high strength, and good thermal resistance to low and high temperatures generated by electric currents and mechanical forces. When the rotor is assembled by press fitting, it also needs to be resistant to wear, fatigue and chemicals, as well as elasticity or toughness. The rotor sleeve should also provide pre-stress for the permanent magnets to ensure that the rotor parts do not separate during operation.

[0010] The rotor sleeve should also exhibit high NOL strength as measured according to ASTM D2290.

[0011] The rotor sleeve of the present invention is intended to solve this technical problem.

[0012] [Brief disclosure of the invention]

[0013] The invention is set out in the appended claims.

[0014] The invention relates to a rotor sleeve as defined in claims 1-19.

[0015] The invention also relates to a method for producing such a rotor sleeve as defined in claims 20-27.

[0016] The invention also relates to an electric machine as defined in claim 28 .

[0017] The invention also relates to a rotor as defined in claim 29 .

[0018] The invention also relates to the use as defined in any of claims 30-32.

[0019] The invention also relates to a strip as defined herein for producing a rotor sleeve, in particular a rotor sleeve as defined herein and in the claims.

[0020] These topics are now defined in more detail below. [Drawings]

[0021] Figure 1 A rotor sleeve according to the invention is shown. Figure 1 It refers to a rotor around which a rotor sleeve is arranged.

[0022] Figure 2 Indicates the rotor sleeve separated from the rotor.

[0023] Figure 3 A method (M1) is presented in which the strip is wound around a rotating mandrel (hoop winding). W is the width of the strip, D is the diameter of the mandrel and L = π D. The angle α is defined by the following relationship: sin α = W / L.

[0024] Figure 4 Method (M1) is shown in more detail, where a strip is wrapped around a rotating mandrel and a laser is used to locally heat the strip. (1): Strip; (2) Contact pressure roller; (3): Laser; (4): Mandrel.

[0025] Figure 5 Method (M1) is shown in more detail, in which a strip is wound around a rotating mandrel and the strip is locally heated using a heat source. (1): heat source; (2): incoming strip; (3): heat flow; (4): pressure roller; (5): engagement point; (6): already stacked strip; (7): surface of the mandrel; (8): arrows indicate tensioning of the strip during winding.

[0026] [General definition]

[0027] Unless otherwise indicated, the percentages are given by weight (wt.%). As is customary in the art, it must be added that the fiber content can also be expressed as a percentage by volume (vol.%) and calculated according to the following equation:

[0028]

[0029] The proportion of the repeating units in the polymer is given in mol. % relative to the total number of moles of repeating units in the polymer.

[0030] When a numerical range is indicated, the endpoints of the range are included.

[0031] The expression "rotor sleeve" is generally used to identify a tubular hollow part designed to be fitted around the rotor of an electric machine.

[0032] Tg indicates the glass transition temperature. It is conveniently measured by differential scanning calorimetry (DSC) according to ASTM D3418.

[0033] Tm and Hm indicate melting temperature and heat of fusion, respectively. They are conveniently measured by DSC according to ASTM D3418. It should be noted that the crystallinity of the strip or thermoplastic composite of the rotor sleeve is measured at the 1st ramp (see, for example, the experimental part).

[0034] [Disclosure of the invention]

[0035] The present invention relates to a rotor sleeve made of or comprising a thermoplastic composite material (TPC) as defined herein. The TPC comprises or consists of: (1) a polymer matrix (P) as defined herein; and (2) continuous fibers as defined herein.

[0036] Typically, the rotor sleeve is hollow and substantially cylindrical. Its cross section is usually circular.

[0037] The thickness of the rotor sleeve is typically between 0.1 and 20.0 mm, preferably between 0.1 and 5.0 mm, preferably between 0.1 and 3.0 mm, preferably between 0.1 and 2.0 mm. The thickness of the rotor sleeve is preferably between 0.5 and 2.0 mm.

[0038] The diameter of the rotor sleeve with a substantially circular cross section is typically between 20.0 mm and 500.0 mm. Larger diameters exist, in particular with diameters of up to 10.0 mm.

[0039] The invention also relates to an electric machine, such as a motor or a generator, comprising:

[0040] -stator;

[0041] - a rotor disposed within the stator and configured to rotate relative to the stator;

[0042] Wherein a rotor sleeve as disclosed herein is arranged circumferentially around the rotor.

[0043] The invention further relates to a rotor of an electric machine, such as a motor or a generator, in which a rotor sleeve according to the invention is arranged circumferentially around a magnet.

[0044] The invention also relates to the use of a thermoplastic composite material (TPC) as defined herein for the preparation of a rotor sleeve.

[0045] The thermoplastic composite material (TPC) comprises or consists of:

[0046] (1) a polymer matrix (P); and

[0047] (2) Continuous fibers;

[0048] Wherein the polymer matrix (P) comprises or consists of:

[0049] at least one thermoplastic polymer having a Tg above 90°C and selected from the group consisting of polyaryletherketone (PAEK), polyphthalamide (PPA), polyamide-imide (PAI), polyphenylene sulfide (PPS) and blends of two or more of said polymers;

[0050] optionally at least one plastic additive; and

[0051] Wherein the continuous fibers are selected from the group consisting of:

[0052] Continuous carbon fiber (CF), and

[0053] ·Continuous glass fiber (GF).

[0054] The continuous fibers are embedded in and in contact with the polymer matrix (P). The function of the continuous fibers is to reinforce the polymer matrix (P).

[0055] According to an embodiment, the polymer matrix (P) consists essentially of or consists of at least one thermoplastic polymer as defined herein and optionally at least one plastic additive.

[0056] The proportion of continuous fibers in the thermoplastic composite (TPC) is generally between 30.0 and 80.0 wt.%, based on the total weight of the thermoplastic composite (TPC). The proportion of polymer matrix (P) in the thermoplastic composite (TPC) is generally between 20.0 and 70.0 wt.%, based on the total weight of the thermoplastic composite (TPC).

[0057] The ratio of fibers is preferably at least 130.0 g / m 2 The ratio can be between 130.0 and 160.0 g / m 2 between.

[0058] The thermoplastic polymer or blend of thermoplastic polymers in the thermoplastic composite (TPC) is preferably semi-crystalline.

[0059] The continuous fibers are typically in the form of tows.

[0060] The thermoplastic polymer or blend of thermoplastic polymers preferably exhibits a heat of fusion (Hm) of at least 5.0 J / g, more preferably at least 10.0 J / g or at least 15.0 J / g. The heat of fusion (Hm) is determined by DSC. More particularly, the heat of fusion is determined as the area under the melting endotherm during the second heating scan.

[0061] The thermoplastic polymer preferably exhibits a melting temperature (Tm) of at least 250° C., preferably at least 300° C. Tm is determined by DSC. More particularly, Tm is determined on the second heating scan.

[0062] Preferred embodiment (E): According to a preferred embodiment (E), the thermoplastic polymer in the polymer matrix (P) is a polyaryletherketone (PAEK) or a blend of more than one PAEK. According to this embodiment (E), the thermoplastic polymer typically exhibits a Tg of at least 140°C.

[0063] According to the present invention and according to embodiment (E), the thermoplastic polymer is selected from the group consisting of poly(etheretherketone) (PEEK), poly(etherketoneketone) (PEKK), poly(etherketone) (PEK), poly(etheretherketoneketone) (PEEKK), PEDEKK, PEEK-PEDEK, PEEK-PEoEK and blends of two or more of said polymers.

[0064] Thus, the thermoplastic composite material (TPC) more particularly comprises or consists of:

[0065] (1) a polymer matrix (P); and

[0066] (2) Continuous fibers,

[0067] Wherein the polymer matrix (P) comprises or consists of:

[0068] At least one thermoplastic polymer selected from the group consisting of poly(etheretherketone) (PEEK), poly(etherketoneketone) (PEKK), poly(etherketone) (PEK), poly(etheretherketoneketone) (PEEKK), PEDEKK, PEEK-PEDEK, PEEK-PEoEK, and blends of two or more of said polymers.

[0069] Optionally at least one plastic additive;

[0070] Wherein the continuous fibers are selected from the group consisting of:

[0071] Continuous carbon fiber (CF), and

[0072] ·Continuous glass fiber (GF).

[0073] According to the invention and according to embodiment (E), the thermoplastic polymer may more particularly be PEEK or a blend of at least one PEEK and at least one thermoplastic polymer other than PEEK and selected from the group consisting of poly(etherketoneketone) (PEKK), poly(etherketone) (PEK), poly(etheretherketoneketone) (PEEKK), PEDEKK, PEEK-PEDEK and PEEK-PEoEK. The relative proportions by weight of the one or more PEEK / one or more thermoplastic polymers other than PEEK in the blend may be between 50 / 50 and 99 / 1.

[0074] The thermoplastic polymer of the polymer matrix (P) may be any of the PAEK disclosed in this list. The thermoplastic polymer of the polymer matrix (P) is preferably PEEK.

[0075] Details and examples are given below for thermoplastic polymers that may be used in thermoplastic composites (TC).

[0076] The continuous fibers are preferably continuous carbon fibers.

[0077] Preparation of rotor sleeve : The rotor sleeve can be produced according to two methods (M1) and (M2). In both methods, the rotor sleeve is produced by winding a tape of thermoplastic composite material (TPC).

[0078] Method (M1): Assembly by press fitting

[0079] The rotor sleeve can be prepared by a method (M1) comprising the following steps:

[0080] Step a): winding a tape of thermoplastic composite material (TPC) on a rotating mandrel to form a plurality of layers of thermoplastic composite material (TPC) around the mandrel;

[0081] Step b): Separating the formed rotor-sleeve from the mandrel.

[0082] In step a), the strip is wound around a rotating mandrel. The diameter of the mandrel corresponds substantially to the inner diameter of the rotor sleeve. The strip is melted by a specific heat source near the meshing point (i.e. where the incoming strip comes into contact with the previous ply) to allow subsequent consolidation (see Figure 5). At the meshing point, the tape is heated at a temperature sufficient to melt the polymer matrix (P) of the TPC. T is generally greater than or equal to (≥) Tm+20°C, where Tm is the melting temperature of the thermoplastic polymer. If the matrix contains m kinds of thermoplastic polymers, Tm is the melting temperature of the thermoplastic polymer with the highest Tm. The heat source can be a hot gas torch, a laser or an infrared source. The temperature is usually measured continuously by a pyrometer or an infrared camera to control the heat source. At the same time, the entire piece can be compacted by a roller made of metal or non-metallic (typically silicone) material to create a close contact between the plies. The actual pressing force applied to the part is a combination of the tensile force applied to the incoming tape and the pressure ensured by the roller against the stack. The pressing force and the tensile force applied to the tape are controlled by a combination of force sensors. The same procedure is repeated until the desired number of plies are stacked to give the rotor sleeve the desired thickness. The combination of temperature and pressure ensures in-situ consolidation of the composite part without the need for further consolidation steps. Figure 4 The laser winding method is demonstrated in .

[0083] After the formed sleeve is removed from the mandrel, it can be machined and trimmed to produce a sleeve with the desired length and surface roughness (Ra). Once completed, the rotor sleeve can be press-fitted around the rotor. The purpose of the press-fit is to provide sufficient radial compressive stress to compensate for the high centrifugal forces generated by the rotation of the rotor, thereby allowing the motor to achieve high speeds and high power levels. The compressive stress is here generated by the interference fit between the permanent magnets and the sleeve.

[0084] Method (M2): Direct winding

[0085] The rotor sleeve can also be prepared by another more direct method (M2), which includes the steps of winding a tape of thermoplastic composite material (TPC) on the rotor to form a plurality of layers of thermoplastic composite material (TPC) around the rotor.

[0086] For process (M1), the tape is heated at a temperature T sufficient to melt the polymer matrix (P) of the TPC. T is generally greater than or equal to (≥) Tm+20°C, where Tm is the melting temperature of the thermoplastic polymer. If the matrix comprises several thermoplastic polymers, Tm corresponds to the melting temperature of the thermoplastic polymer with the highest Tm. The heat source is the same as disclosed above for process (M1).

[0087] In method (M2), several layers of sleeve are directly overwound on the permanent magnet rotor. This method is characterized by ultra-high tension applied to the incoming strip. This pre-tension is a key parameter to provide sufficient compressive stress to offset the large centrifugal forces and ensure that the permanent magnets remain on the rotor shaft. The maximum tension of the carbon fiber is obtained by applying a huge winding tension. This pre-tension produces a hoop stress that acts as a compressive stress, thereby keeping the in-situ consolidated thermoplastic composite sleeve in place on the permanent magnet rotor.

[0088] For both methods, the fibers may be wound around a mandrel or around a rotor according to a predetermined pattern (eg, hoop winding or cross winding).

[0089] In method (M2), a tension (also called pre-tension) is usually applied to the fibers before winding. This makes it possible to obtain a rotor sleeve that exhibits sufficient radial compressive stress to compensate for the high centrifugal forces during the rotation of the rotor.

[0090] The rotor sleeve primarily requires resistance to circumferential stresses. For this purpose, the strip is usually wound almost perpendicular to the mandrel axis, which means that the winding angle is close to 90°. This type of circumferential winding is called "hoop winding". In some cases, cross-ply winding can be applied. Because long tubes are manufactured instead of rings, the hoop lay-up direction is not a pure 90°, but a slight angle is required to avoid overlapping of the strips. The angle to be applied depends on the width of the strip (typically 200°). 1 / 4 , 1 / 2 or 1 inch) and the mandrel diameter, such as Figure 3 A compromise is usually found between mechanical performance with respect to circumferential loads (which requires minimizing the fiber angle and therefore the tape width) and productivity (which requires using wider tapes to minimize the manufacturing cycle time). Furthermore, in the case of assembly by press fitting, the increased angle can help to increase the stability of the sleeve and prevent delamination.

[0091] The thickness of the rotor sleeve is a critical factor since the performance and efficiency of the rotor is increased by reducing the air gap between the rotor and the stator. Therefore, the thinnest sleeve (ie 0.5 to 2.0 mm) is preferred.

[0092] The tape used in both methods is typically unidirectional tape.

[0093] Strip preparation: Tapes of thermoplastic composites (TPC) are prepared by known methods of impregnating continuous fibers with a polymer matrix (P). The tapes are usually prepared by a method comprising the following steps:

[0094] a)- contacting the continuous fibers, in particular the continuous carbon fibers, with a thermoplastic polymer of the polymer matrix or a blend of the one or more thermoplastic polymers and / or the one or more additives;

[0095] b) - heating the structure obtained in the previous step at a temperature sufficient to melt the polymer or polymers of the polymer matrix.

[0096] During step a) and / or step b), pressure is generally exerted on the structure.

[0097] When the polymer matrix (P) comprises a blend of a thermoplastic polymer and / or at least one plastic additive, it is advantageous to prepare a blend of the ingredients before step a). This ensures a uniform blend of these ingredients in the TPC. The blend can be prepared by blending powders or by melt mixing. Melt mixing is preferred because it ensures a tighter blend of the one or more thermoplastic polymers and / or the one or more plastic additives. Melt mixing can be carried out in a melt mixing device. Any melt mixing device known to those skilled in the art can be used. Suitable melt mixing devices can be selected, for example, from a list consisting of a kneader, a Banbury mixer, a single screw extruder and a twin screw extruder. Conventional melt mixing devices are single screw extruders or twin screw extruders. The one or more polymers and the one or more plastic additives (if any) can be introduced into the melt mixing device in any order. If step a) is carried out via a slurry method, the blend prepared by the melt mixing method is ground to obtain particles of a blend having an appropriate size.

[0098] For step a), various methods can be used to contact the thermoplastic polymer or blend with the continuous fibers. The continuous fibers should be uniformly impregnated with the thermoplastic polymer or blend. Uniform impregnation of all fibers allows the production of tapes with optimized mechanical properties.

[0099] Step a) can be carried out by electrostatic powder coating, foam coating or by impregnation with the polymer or polymers in solution or in slurry (slurry process).

[0100] Slurry method: The slurry process is a convenient method for bringing continuous fibers into intimate contact with a polymer matrix (P). The slurry process is based on contacting the fibers with a slurry of particles of a thermoplastic polymer or blend suspended in a liquid phase. The slurry-impregnated fibers are then heated to a temperature sufficient to evaporate the slurry liquid and melt the polymer or polymers of the polymer matrix.

[0101] The size of the particles in the slurry should preferably be low enough to allow better impregnation of the fibers. A grinding process is a convenient way to obtain these particles of appropriate size. The liquid phase can be water, an organic liquid or a mixture of water and an organic liquid.

[0102] The median Dv50 (median value determined from the volume distribution) of the particles in the slurry is typically between 1 and 300 μm. The Dv50 can be measured by laser scattering.

[0103] A surfactant may be present in the slurry. The term "surfactant" means any organic compound having a hydrophilic portion and a lipophilic portion and capable of dispersing particles in a liquid phase and maintaining them in suspension with or without agitation.

[0104] The heating step may be conducted at a first temperature sufficient to allow evaporation of the slurry liquid and at a second temperature sufficient to melt the one or more polymers of the polymer matrix.

[0105] More information on the slurry process is provided, for example, in US 4,792,481 or in the following document: "Wet impregnation as route to unidirectional carbon fibre reinforced thermoplastic composites manufacturing", Plastics Rubber and Composites, March 2011, Vol. 40(2), pp. 100-107 (DOI: 10.1179 / 174328911X12988622801098).

[0106] The slurry method disclosed in the experimental section can be used.

[0107] PAEK polymer

[0108] Polyaryletherketone (PAEK) polymers refer to any polymer containing more than 50.0 mol% of repeating units (R PAEK ) of polymers, these repeating units (R PAEK ) are linked to each other via a -O- or -C(=O)- group and are selected from the group consisting of units having the following formulae (JA) to (JQ):

[0109]

[0110]

[0111] in:

[0112] -R' j’ Each R' of is the same as or different from each other and is selected from the group consisting of halogen, alkyl, alkenyl, alkynyl, aryl, ether, thioether, carboxylic acid, ester, amide, imide, alkali metal or alkaline earth metal sulfonate, alkyl sulfonate, alkali metal or alkaline earth metal phosphonate, alkyl phosphonate, amine and quaternary ammonium; and

[0113] -j' is zero or an integer in the range 1 to 4.

[0114] In the repeating unit (R PAEK ), the corresponding phenylene moieties may independently have the same PAEK ) in the other parts. Preferably, the phenylene part has a 1,3-linkage or a 1,4-linkage.

[0115] j' is preferably zero at each occurrence.

[0116] The repeating unit (R PAEK ) is advantageously at least 60.0 mol%, or at least 70.0 mol%, or at least 80.0 mol%, or at least 90.0 mol%, or at least 95.0 mol%, or at least 99.0 mol%. According to an embodiment, all repeating units of the PAEK polymer are repeating units (R PAEK ).

[0117] PEEK: As used herein, "poly(etheretherketone) (PEEK)" means any polymer wherein more than 96.0 mol% of the repeating units have the formula (J'-A):

[0118]

[0119] The proportion of repeating units (J'-A) in PEEK may more particularly be at least 99.0 mol %. According to an embodiment, all repeating units of PEEK are repeating units (J'-A).

[0120] The melt flow rate of PEEK as measured according to ASTM D1238 (400° C., 2.16 kg) may be between 1.0 and 50.0 g / 10 min.

[0121] An example of PEEK that may conveniently be used is Ketaspire KT880 or KT820 commercialised by Solvay. Ketaspire KT880 UFP commercialised by Solvay may also conveniently be used.

[0122] PEKK:As used herein, "poly(etherketoneketone) (PEKK)" means any polymer wherein more than 95.0 mol% of the repeating units are a combination of repeating units having formula (J'-B) and formula (J"-B):

[0123]

[0124] The proportion of repeating units (J′-B) and (J″-B) in PEKK can more particularly be at least 99.0 mol %. According to an embodiment, all repeating units of PEKK are repeating units (J′-B) and (J″-B).

[0125] The molar ratio (J'-B) / (J"-B) is selected so that the polymer is semi-crystalline. The molar ratio (J'-B) / (J"-B) is preferably greater than 60 / 40. The molar ratio (J'-B) / (J"-B) is preferably between 60 / 40 and 90 / 10 or between 65 / 35 and 80 / 20.

[0126] An example of a PEKK that may be used is Kepstan 7002 commercialized by Arkema.

[0127] PEK: As used herein, "poly(etherketone) (PEK)" means any polymer wherein more than 95.0 mol% of the repeating units have the formula (J'-C):

[0128]

[0129] The proportion of repeating units (J′-C) in PEK may more particularly be at least 99.0 mol %. According to an embodiment, all repeating units of PEK are repeating units (J′-C).

[0130] PEEKK: As used herein, "poly(etheretherketoneketone) (PEEKK)" means any polymer wherein more than 95.0 mol% of the repeating units have the formula (J'-M):

[0131]

[0132] The proportion of repeating units (J′-M) in PEEKK may more particularly be at least 99.0 mol %. According to an embodiment, all repeating units of PEEKK are repeating units (J′-M).

[0133] PEDEKK: "PEDEKK" means any repeating unit (R PAEK ) is a polymer having a combination of repeating units of formula (J'-Q) and (J"-Q):

[0134]

[0135] The proportion of repeating units (J′-Q) and (J″-Q) in PEDEKK may more particularly be at least 99.0 mol %. According to an embodiment, all repeating units of PEDEKK are repeating units (J′-Q) and (J″-Q).

[0136] PEEK-PEDEK: PEEK-PEDEK means any polymer in which more than 95.0 mol% of the repeating units are a combination of repeating units having the formula (J'-A) and (J'-D):

[0137]

[0138] The proportion of repeating units (J'-A) and (J'-D) in PEEK-PEDEK may more particularly be at least 99.0 mol %. According to an embodiment, all repeating units of PEEK-PEDEK are repeating units (J'-A) and (J'-D).

[0139] The molar ratio (J'-A) / (J'-D) may be between 95 / 5 and 60 / 40 or between 90 / 10 and 70 / 30.

[0140] PEEK-PEoEK: PEEK-PEoEK means any polymer in which more than 95.0 mol% of the repeating units are a combination of repeating units having the formula (J'-A) and (J"-A):

[0141]

[0142] The molar ratio (J'-A) / (J"-A) may be between 95 / 5 and 5 / 95. The molar ratio may preferably be between 70 / 30 and 95 / 5.

[0143] All PAEKs disclosed in this section are prepared by conventional polycondensation techniques well known in the art, in particular by a nucleophilic route or by an electrophilic route. More specifically, PAEKs can be prepared by nucleophilic aromatic substitution in which diaryl ether linkages are obtained. The polycondensation is usually carried out in a solvent such as diphenyl sulfone at 300° C. or higher with the aid of a base such as Na 2 CO 3 and / or K 2 CO 3 ). Some details about polycondensation involving nucleophilic substitution can be found in, for example, US 4,176,222 or WO 2021 / 008983. For example, PEEK is prepared by the polycondensation of 4,4-difluorobenzophenone and hydroquinone via a nucleophilic route.

[0144] PAEK polymers can be prepared by Friedel-Crafts electrophilic substitution in which diaryl ketone linkages are obtained. The polycondensation is usually carried out in a solvent at temperatures below 150°C with the aid of a Lewis acid such as AlCl 3 ). Some details on polycondensation involving Friedel-Crafts electrophilic substitution can be found in, for example, US 4,841,013, US 4,816,556, WO 2011 / 004164 and WO 2014 / 013202. For example, PEKK can be prepared by polycondensation of 4,4-dichlorobenzene, iso- and terephthaloyl chlorides via an electrophilic route.

[0145] PPS Polymer

[0146] Polyphenylene sulfide (PPS) means any polyphenylene sulfide containing at least 50.0 mol.% of repeating units (R PPS ) of polymers:

[0147]

[0148] The proportion of repeating units (L) may be at least 60.0 mol.%, or at least 70.0 mol.%, or at least 80.0 mol.%, or at least 90.0 mol.%, or at least 95.0 mol.%, or at least 99.0 mol.%.

[0149] According to an embodiment, all repeating units (R PPS ) are all repeating units having formula (L).

[0150] The PPS polymer is prepared by conventional polycondensation techniques well known in the art. More specifically, the PPS polymer can be prepared by heating a reaction mixture comprising at least one p-dihalobenzene compound (such as p-dichlorobenzene) and a sulfur compound in a polar aprotic solvent. The sulfur compound is typically an alkali metal sulfide, such as Na 2 S. In some embodiments, the alkali metal sulfide is generated in situ from an alkali metal hydrosulfide and an alkali metal hydroxide. Na2S can be generated in situ from NaSH and NaOH. The temperature at which the polymerization occurs is typically at least 150°C, more particularly at least 200°C.

[0151] The melt flow rate of PPS as measured according to ASTM D1238 (316° C., 5 kg) may be between 1.0 and 50.0 g / 10 min.

[0152] An example of a PPS that may be conveniently used is Ryton QA200N commercialized by Solvay.

[0153] Polyphthalamide (PPA) polymer

[0154] A PPA polymer is any polyamide in which more than 55.0 mol %, preferably at least 75.0 mol %, preferably at least 99.0 mol % of the repeating units (R PA ) is the result of the condensation of an aromatic phthalic acid selected from the group consisting of terephthalic acid, isophthalic acid and a combination of the two phthalic acids with at least one diamine.

[0155] According to an embodiment, substantially all repeating units are repeating units (R PA ).

[0156] According to an embodiment, the repeating unit of PPA consists of the repeating unit (R PA )composition.

[0157] The diamines may be aromatic or aliphatic.

[0158] The diamine is preferably an aliphatic diamine selected from the group consisting of 1,6-hexamethylenediamine, 1,9-nonanediamine, 1,10-diaminodecane, 2-methyloctanediamine, 2-methyl-1,5-pentanediamine or 1,4-diaminobutane. The diamine may more particularly be 1,6-hexamethylenediamine.

[0159] The polyamide (PPA) can more particularly be selected from the group consisting of the following polyamides: 6T / 66; 6T / 6I; 6T / 6I / 66; 6T / BACT / 10T, wherein BAC is 1,3-BAC and / or 1,4-BAC, preferably 1,3-BAC; a polyamide having repeating units (RPA) formed by the polycondensation of a monomer mixture consisting of T, 1,4-cyclohexanedicarboxylic acid, 1,6-diaminohexane and 1,10-diaminodecane; a polyamide having repeating units (RPA) formed by the polycondensation of a monomer mixture consisting of T, 1,4-cyclohexanedicarboxylic acid, 1,6-diaminohexane and 1,9-diaminononane and combinations thereof.

[0160] An example of a polyphthalamide that may conveniently be used is Amodel A-8004 commercialized by Solvay.

[0161] PAI polymer

[0162] The polyamide-imide (PAI) polymer is a polymer comprising more than 50.0 mol% of a repeating unit (R PAI ) of polymers:

[0163]

[0164] as well as

[0165]

[0166] Most preferably, the polymer (PAI) comprises more than 90.0 mol % of the repeating units (R PAI Still more preferably, it contains no other than the repeating unit (R PAI ) other than the repeating unit.

[0167] An example of a PAI polymer that may be conveniently used is Torlon 4203L commercialized by Solvay.

[0168] Plastic Additives

[0169] The polymer matrix may also contain at least one plastic additive.

[0170] The one or more plastic additives are typically blended with the one or more thermoplastic polymers.

[0171] The plastic additive may be selected from the group consisting of colorants (e.g., dyes and / or pigments), UV stabilizers, heat stabilizers, antioxidants, acid scavengers, processing aids, internal and / or external lubricants, flame retardants, smoke suppressants, antistatic agents, anti-blocking agents, and any combination thereof.

[0172] The proportion of the one or more plastic additives in the polymer matrix (P) is generally less than 20.0% by weight, based on the total weight of the polymer matrix (P).

[0173] Continuous Fiber

[0174] Thermoplastic composites (TPCs) comprise continuous fibers as disclosed herein.

[0175] Thermoplastic composites (TPCs) comprise fibers, particularly continuous carbon fibers, substantially all of which are oriented at a zero degree fiber angle.

[0176] As used herein, the term "carbon fiber" is intended to include graphitized, partially graphitized and ungraphitized carbon fibers, and mixtures thereof. Carbon fibers can be obtained by heat treatment and pyrolysis of different polymer precursors such as rayon, polyacrylonitrile (PAN), aromatic polyamide or phenolic resin; carbon fibers can also be obtained from asphalt materials. Carbon fibers are preferably selected from the group consisting of: PAN-based carbon fibers, asphalt-based carbon fibers, graphite fibers and mixtures thereof. Graphitized fibers are typically obtained by high-temperature pyrolysis of carbon fibers (usually above 2000°C), in which the carbon atoms are arranged in a manner similar to the graphite structure.

[0177] The continuous fibers typically exhibit an aspect ratio (length / diameter ratio) of greater than or equal to 500, more typically greater than or equal to 5,000.

[0178] Continuous fibers are typically in the form of tows (sometimes referred to as rovings). A tow generally refers to a plurality of continuous individual filaments that are optionally coated with an organic coating.

[0179] Carbon fiber tow is made of thousands of individual carbon fiber filaments that are bundled. Carbon fiber tow is available in many different sizes, which are typically 3K, 6K, 12K, 24K or higher, referring to the number of thousands of filaments (3K tow is made of 3000 individual carbon filaments). In the context of the present invention, the size of the carbon fiber tow is preferably between 1K and 350K.

[0180] Carbon fiber tows with sizes below 14K allow for the production of thin rotor sleeves. Thus, the size may be between 10K and 14K.

[0181] Carbon fiber tow sizes above 14K allow for faster winding of the tape around the mandrel.

[0182] The tow of carbon fiber preferably exhibits a tensile strength greater than or equal to 3500 MPa and / or a tensile modulus greater than or equal to 200 GPa. The tensile strength may be greater than or equal to 5000 MPa. The tensile modulus may be greater than or equal to 250 GPa. It is also preferred that the carbon fiber is an aligned continuous carbon fiber. The tensile strength and tensile modulus may be measured according to ASTM D4018.

[0183] In the case of unidirectional tapes, as used herein, "tape" means a strip of material having longitudinally extending fibers that are aligned along a single axis of the strip material. Tapes can be manufactured with large widths (50 mm to 1 m or more) made from several tows that are properly spread and then slit in the form of narrow strips for automated fiber placement. Narrow ribbons made from a single tow can also be manufactured, which has the advantage that the carbon fibers are not damaged by the slitting process. Tapes are advantageous because they can be used in manual or automated layup processes to produce composites with relatively complex shapes.

[0184] Mechanical, physical and physicochemical properties of unidirectional tapes of thermoplastic composites

[0185] The strip can also be defined by a combination of mechanical, physical / morphological and physicochemical properties. These properties are given for the strip used to make the rotor sleeve.

[0186] The tape typically exhibits a tensile strength (along the fiber direction at 0 degrees) of at least 2000 MPa. The tensile strength is preferably at least 2400 MPa, preferably at least 2700 MPa, preferably at least 2800 MPa. The tensile strength is measured according to ASTM D3039. The tensile strength is typically at most 4500 MPa.

[0187] The unidirectional tape may also exhibit a tensile strain (along the fiber direction at 0 degrees) of at least 0.5%, preferably at least 1.0%, preferably at least 1.5%. The tensile strain is measured according to ASTM D3039. The tensile strain is typically at most 5.0%.

[0188] The tape may also exhibit a tensile modulus (along the fiber direction at 0 degrees) of at least 100 GPa, preferably at least 150 GPa, preferably at least 170 GPa. The tensile modulus is measured according to ASTM D3039.

[0189] The tape may also exhibit a maximum of 5.0 10 -6 mm / mm / K, preferably up to 2.0 10 -6 mm / mm / K, preferably up to 1.010 -6 Coefficient of thermal expansion in mm / mm / K. The values ​​are specified in particular for temperatures between ambient temperature and 200° C.

[0190] The strip is also characterized by its morphology:

[0191] Thickness and Thickness Consistency: The thickness of the tape may be lower than or equal to 200 μm. The thickness may more particularly be lower than 120 μm.

[0192] Furthermore, the variation of the strip thickness is preferably lower than and equal to 10.0%, preferably lower than and equal to 5.0%, which variation is defined as the standard deviation s of the strip thickness. s has the usual statistical meaning and is defined by: Wherein X corresponds to each measured value of the thickness, μ is the arithmetic mean and N is the total number of measurements performed. N is at least 10, preferably at least 20, preferably at least 50. The lower s is, the better the mechanical properties of the rotor sleeve.

[0193] Roughness Ra: The thermoplastic composite tape (TPC) preferably exhibits a surface roughness Ra lower than and equal to 10.0 μm. The surface roughness Ra is more particularly between 1.0 and 7.0 μm, preferably between 1.0 and 5.0 μm. The surface roughness Ra can be measured according to ISO 4288 and ISO 4287. The slurry process makes it possible to obtain such a low Ra. Low Ra enables better processability and better in-situ consolidation.

[0194] width: The width of the strip should be obtained according to the laying process. The most common slit strip width is 1 / 4 , 1 / 2 , 1, 1 1 / 4 , 1 1 / 2 and 2 inches. Narrow strips are usually selected (i.e. 1 / 4 ”) are used for 3D parts with small diameters, in some cases to minimize the amount of material and associated material scrap / waste, or in the case of tape winding to limit the angle of the hoop winding. Larger tapes are used to increase production speeds. In the case of slit tapes, some fibers are cut or damaged during slitting, thereby increasing the width variation along the entire tape.

[0195] Tow prepreg (preg) is another type of tape that can be used to prepare the rotor sleeve of the present invention. Tow prepreg is a continuous composite tape made of one or two single tows of continuous carbon fiber. Each tow of carbon fiber can have 12K, 24K, 36K or 50K filaments. Therefore, the number of filaments in the tow prepreg is generally between 10K and 60K. For tow prepreg, it is important to maintain a constant square cross-section along the entire tape. Tapes or tow prepregs with low width variations will make automatic placement easier and more efficient (placement speed), thereby avoiding gaps or overlaps that reduce the performance of composite parts.

[0196] Porosity: During the preparation of the tape, air and volatiles may be trapped in the material, resulting in porosity or voids within the plies, which may affect the mechanical properties of the tape. The porosity of the tape is preferably lower than and equal to 2.0 vol%, preferably lower than and equal to 0.5 vol%, preferably lower than and equal to 0.2 vol%. The porosity is measured by microscopic analysis, which allows visualization of the shape and size of the voids. Non-destructive inspections such as infrared thermography and ultrasonic inspection may also be applied.

[0197] Characteristics of the rotor sleeve

[0198] The rotor sleeve of the present invention preferably exhibits a hoop tensile strength (unnotched) of at least 2000 MPa, preferably at least 2100 MPa, preferably at least 2200 MPa, preferably at least 2300 MPa, preferably at least 2400 MPa, measured according to ASTM D2290 (Procedure B).

[0199] Furthermore, for embodiment (E), the thermoplastic composite material preferably exhibits a crystallinity ratio Xc of at least 25.0%, Xc = [Hm in J / g] / [130 J / g] x 100, where Hm is the heat of fusion of the thermoplastic composite material of the sleeve, expressed in J / gPAEK.

[0200] Hm is measured by DSC according to ASTM D3418 with the following thermal program: ramp from 40° C. to 380° C. at 10° C. / min, cooling until 40° C., second ramp until 380° C. Hm is determined from the 1st ramp.

[0201] According to a preferred embodiment, the rotor sleeve of the present invention is made of or comprises a thermoplastic composite material (TPC), and the thermoplastic composite material (TPC) comprises or consists of:

[0202] (1) a polymer matrix (P); and

[0203] (2) Continuous carbon fiber,

[0204] Wherein the polymer matrix (P) comprises or consists of:

[0205] At least one thermoplastic polymer selected from the group consisting of poly(etheretherketone) (PEEK), poly(etherketoneketone) (PEKK), poly(etherketone) (PEK), poly(etheretherketoneketone) (PEEKK), PEDEKK, PEEK-PEDEK, PEEK-PEoEK, and blends of two or more of said polymers.

[0206] Optionally at least one plastic additive;

[0207] And among them:

[0208] The rotor sleeve exhibits a hoop tensile strength (unnotched) of at least 2000 MPa, preferably at least 2100 MPa, preferably at least 2200 MPa, preferably at least 2300 MPa, preferably at least 2400 MPa, measured according to ASTM D2290 (Procedure B); and / or

[0209] The thermoplastic composite material preferably exhibits a crystallinity ratio Xc of at least 25.0%, Xc = [Hm in J / g] / [130 J / g] × 100, where Hm is the heat of fusion of the thermoplastic composite material of the sleeve, expressed in J / g PAEK, and Hm is measured by DSC according to ASTM D3418 with the following thermal program: ramp from 40°C to 380°C at 10°C / min, cooling until 40°C, second ramp until 380°C, Hm is determined from the 1st ramp.

[0210] The thermoplastic polymer of the polymer matrix (P) typically exhibits a Tg of at least 140°C.

[0211] Xc is preferably at least 27.0%, preferably at least 28.0%, preferably at least 29.0%. Xc is usually below 50.0%. 130 J / g is taken as a reference value and corresponds to the heat of fusion of completely crystalline polyetheretherketone.

[0212] All details provided previously apply equally to this preferred embodiment. In particular, the thermoplastic polymer may be PEEK or a blend of at least one PEEK and at least one thermoplastic polymer other than PEEK and selected from the group consisting of poly(etherketoneketone) (PEKK), poly(etherketone) (PEK), poly(etheretherketoneketone) (PEEKK), PEDEKK, PEEK-PEDEK and PEEK-PEoEK.

[0213] [Experimental part]

[0214] Polymers used: Ketaspire KT880 UFP (Ultrafine Powder) from Solvay; its melt viscosity is 0.15 kPa-s at 1000 / s at 400°C (ASTM D3835). Dv50 = 10.5 μm.

[0215] Continuous carbon fiber used:

[0216] CF1: From Hexcel IM7. See https: / / www.hexcel.com / user_area / content_media / raw / IM7_HexTow_DataSheet.pdf. Tensile strength: 5688MPa; Weight length: 0.446g / m; Tow cross-sectional area: 0.25mm 2 ; Filament diameter: 5.2μm.

[0217] CF2: Another CF used has a 12K high strength standard modulus and exhibits a tensile strength of 5500 MPa, a tensile modulus of 250 GPa and a tensile strain of 2%. The filament diameter is 7 μm.

[0218] Both CF1 and CF2 are untwisted and untreated.

[0219] Strip preparation method:The tapes are prepared using a slurry process. Tows of carbon fiber are fed from a creel. Spreading rods are used to convert the CF tows into tapes and they are formed into a web before entering the slurry suspension bath. The slurry bath container is filled with an aqueous polymer slurry made by mixing Ketaspire KT-880UFP and water. The CF web captures the polymer powder between the fiber filaments and is powder coated. After the web is guided out of the slurry bath, it enters an oven unit and a melting roller in order to eliminate moisture and impregnate the polymer onto the fibers. Finally, the TPC tapes are collected and wound through a winding machine.

[0220] Table I: Properties of unidirectional strip

[0221]

[0222] X c =[H m,带材 / 130J / g]×100, where H m,带材 is the heat of fusion of the ribbon and is expressed in J / g resin.

[0223] The Tg, Tm and Hm of the strips were determined by DSC analysis of the strips according to ASTM D3418. A full thermal cycle was performed, which included a first heating to 400°C at 10°C / min, cooling to 25°C and a second heating to 400°C. Hm was determined from the 1st ramp.

[0224] The characteristics of the consolidated part produced by tape winding with in-situ consolidation using the previously defined tapes 1-3 are: sex

[0225] The rotor sleeve is produced by tape winding with in-situ consolidation. The layup is a pure 8-layer hoop winding (90°). The ring is about 1 mm thick and has an inner diameter of 146 mm. No trimming is done on the ring edges and there is no notching on the ring.

[0226] Table II

[0227]

[0228] (1) SBS samples were obtained from 1 / 4 "Width slit tape was extracted parallel to the winding direction from a tube wound at a small angle of + / -89°. The tube thickness was approximately 4.5 mm (depending on the instance) and the inner diameter was 146 mm. The specimens conformed to ASTM D2344 dimensions. The setup defined in ASTM D2344 for curved specimens was used, including a flat support with a 12 mm span length and a loading nose of 10 mm diameter (instead of 6 mm as defined in the standard).

[0229] (2) The crystallinity Hm of the sleeve is measured by DSC according to ASTM D3418 with the following thermal program: ramp from 40°C to 380°C at 10°C / min, cooling to 40°C, second ramp to 380°C. c =[H m,套筒 / 130J / g]×100, where H m,套筒 is the heat of fusion of the TPC of the sleeve and is expressed in J / g resin. Hm is determined from the 1st ramp.

Claims

1. A rotor sleeve made of or comprising a thermoplastic composite material (TPC), wherein the thermoplastic composite material (TPC) comprises or consists of: (1) a polymer matrix (P); and (2) Continuous fibers; Wherein the polymer matrix (P) comprises or consists of: at least one thermoplastic polymer having a Tg above 90°C and selected from the group consisting of polyaryletherketone (PAEK), polyphthalamide (PPA), polyamide-imide (PAI), polyphenylene sulfide (PPS) and blends of two or more of said polymers; optionally at least one plastic additive; and Wherein the continuous fibers are selected from the group consisting of: Continuous carbon fiber (CF), and ·Continuous glass fiber (GF).

2. The rotor sleeve according to claim 1, wherein: The thermoplastic polymer of the polymer matrix (P) is selected from the group consisting of poly(etheretherketone) (PEEK), poly(etherketoneketone) (PEKK), poly(etherketone) (PEK), poly(etheretherketoneketone) (PEEKK), PEDEKK, PEEK-PEDEK, PEEK-PEoEK and blends of two or more of said polymers, and preferably exhibits a Tg of at least 140°C.

3. The rotor sleeve according to claim 1, wherein: The thermoplastic polymer of the polymer matrix (P) is PEEK.

4. The rotor sleeve according to any one of claims 1 to 3, wherein: - the proportion of the continuous carbon fibers in the thermoplastic composite material (TPC) is between 30.0 and 80.0 wt.%, based on the total weight of the thermoplastic composite material (TPC); and / or - the proportion of the polymer matrix (P) in the thermoplastic composite material (TPC) is between 20.0 and 70.0 wt.%, based on the total weight of the thermoplastic composite material (TPC); and / or - The fiber ratio is at least 130.0 g / m 2 Or between 130.0 and 160.0 g / m 2 between.

5. A rotor sleeve according to any one of the preceding claims, wherein: The thermoplastic polymer or blend of thermoplastic polymers exhibits a heat of fusion (ΔH) of at least 5.0 J / g, more preferably at least 10.0 J / g or at least 15.0 J / g. f ).

6. A rotor sleeve according to any one of the preceding claims, wherein: The thermoplastic polymer exhibits a melting temperature (Tm) of at least 250°C, preferably at least 300°C.

7. A rotor sleeve according to any one of the preceding claims, wherein: The thermoplastic polymer in the polymer matrix (P) is a polyaryletherketone (PAEK) or a blend of more than one PAEK.

8. The rotor sleeve according to claim 7, wherein: The thermoplastic polymer is PEEK or a blend of at least one PEEK and at least one thermoplastic polymer other than PEEK selected from the group consisting of poly(etherketoneketone) (PEKK), poly(etherketone) (PEK), poly(etheretherketoneketone) (PEEKK), PEDEKK, PEEK-PEDEK and PEEK-PEoEK.

9. The rotor sleeve according to claim 8, wherein: The relative proportions by weight of PEEK(s) / thermoplastic polymer(s) other than PEEK are between 50 / 50 and 99 / 1.

10. A rotor sleeve according to claim 2 or 3 or any one of claims 8 to 9, wherein: - The PEEK is a polymer in which more than 96.0 mol% of the repeating units have the formula (J'-A): - the PEKK is a polymer wherein more than 95.0 mol% of the repeating units are a combination of repeating units of formula (J'-B) and formula (J"-B): - The PEK is a polymer in which more than 95.0 mol% of the repeating units have the formula (J'-C): - the PEEKK is a polymer in which more than 95.0 mol % of the repeating units have the formula (J'-M): - the PEDEKK is a repeating unit (R PAEK ) is a polymer having a combination of repeating units of formula (J'-Q) and (J"-Q): - The PEEK-PEDEK is a polymer wherein more than 95.0 mol% of the repeating units are a combination of repeating units having the formula (J'-A) and (J'-D): - the PEEK-PEoEK is a polymer in which more than 95.0 mol% of the repeating units are a combination of repeating units of formula (J'-A) and (J"-A):

11. A rotor sleeve according to any one of the preceding claims, wherein: The proportion of the one or more plastic additives in the polymer matrix (P) is less than 20.0 wt %, based on the total weight of the polymer matrix (P).

12. The rotor sleeve according to any one of the preceding claims, exhibiting a hoop tensile strength (unnotched) measured according to ASTM D2290 (Procedure B) of at least 2000 MPa, preferably at least 2100 MPa, preferably at least 2200 MPa, preferably at least 2300 MPa, preferably at least 2400 MPa.

13. The rotor sleeve according to claim 2 or claim 3 or a combination of claim 2 or claim 3 and any one of claims 4 to 12, wherein: The thermoplastic composite material (TPC) exhibits a crystallinity ratio Xc of at least 25.0%, preferably at least 27.0%, preferably at least 28.0%, preferably at least 29.0%, Where Xc is defined by the following formula: Xc = [Hm in J / g] / [130 J / g] × 100 Where Hm is the heat of fusion of the thermoplastic composite, expressed in J / g PAEK and measured by DSC according to ASTM D3418 with the following thermal program: ramp from 40°C to 380°C at 10°C / min, cooling until 40°C, second ramp until 380°C, Hm is determined from the 1st ramp.

14. A rotor sleeve according to any one of the preceding claims, wherein: These continuous carbon fibers exhibit a tensile strength greater than or equal to 3500 MPa and / or a tensile modulus greater than or equal to 200 GPa.

15. A rotor sleeve according to any one of the preceding claims, wherein: The thermoplastic composite (TC) comprises continuous carbon fibers, substantially all of which are oriented at a fiber angle of zero degrees.

16. A rotor sleeve according to any one of the preceding claims, in the form of a tubular hollow part designed to fit around a rotor of an electric machine.

17. A rotor sleeve according to any one of the preceding claims, wherein: The size of the carbon fiber tow is between 1K and 350K, preferably 3K, 6K, 12K or 24K.

18. A rotor sleeve according to any one of the preceding claims, wherein: The size of the carbon fiber tow is below 14K or between 10K and 14K.

19. A rotor sleeve according to any one of the preceding claims, produced by winding a tape of the thermoplastic composite material.

20. A method (M1) for preparing a rotor sleeve according to any one of claims 1 to 19, the method (M1) comprising the following steps: Step a): winding a unidirectional tape of a thermoplastic composite material (TPC) on a rotating mandrel to form a plurality of layers of the thermoplastic composite material (TPC) around the mandrel; Step b): Separating the formed rotor-sleeve from the mandrel.

21. A method (M2) for preparing a rotor sleeve as described in any one of claims 1 to 19, the method (M2) comprising the step of winding the unidirectional tape of the thermoplastic composite material on the rotor to form a plurality of layers of the thermoplastic composite material (TPC) surrounding the rotor.

22. The method according to claim 21, wherein: Tension is applied to the fibers prior to winding.

23. The method according to any one of claims 20 to 22, wherein: The tape is in the form of slit tape or tow prepreg.

24. The method according to any one of claims 20 to 23, wherein: The thermoplastic composite material of the tape exhibits a tensile strength (along the fiber direction at 0 degrees and according to ASTM D3039) of at least 2000 MPa, preferably at least 2400 MPa, preferably at least 2800 MPa.

25. The method according to any one of claims 20 to 24, wherein: The thermoplastic composite material of the tape exhibits a tensile strain (along the fiber direction at 0 degrees and according to ASTM D3039) of at least 0.5%, preferably at least 1.0%, preferably at least 1.5%.

26. The method according to any one of claims 20 to 25, wherein: The thermoplastic composite material of the tape exhibits a thermal conductivity of at most 5.0 10 % along the direction of the fibers and measured according to ASTM E831. -6 mm / mm / K, preferably up to 2.0 10 -6 mm / mm / K, preferably up to 1.0 10 -6 Thermal expansion coefficient in mm / mm / K.

27. The method according to any one of claims 20 to 26, wherein: The strip exhibits a surface roughness Ra, measured according to ISO 4287, lower than 10.0 μm, more particularly between 1.0 and 7.0 μm.

28. An electric machine such as a motor or a generator, the electric machine comprising: -stator; - a rotor disposed within the stator and configured to rotate relative to the stator; The rotor sleeve according to any one of claims 1 to 19 is arranged circumferentially around the rotor.

29. A rotor of an electric machine, such as a motor or a generator, wherein a rotor sleeve as claimed in any one of claims 1 to 19 is arranged circumferentially around the rotor.

30. Use of a strip material according to any one of the preceding claims for producing a rotor sleeve.

31. Use of a tape of a thermoplastic composite material (TPC) for producing a rotor sleeve, the thermoplastic composite material (TPC) comprising or consisting of: (1) a polymer matrix (P); and (2) Continuous carbon fiber, Wherein the polymer matrix (P) comprises or consists of: at least one thermoplastic polymer having a Tg above 140°C and selected from the group consisting of poly(etheretherketone) (PEEK), poly(etherketoneketone) (PEKK), poly(etherketone) (PEK), poly(etheretherketoneketone) (PEEKK), PEDEKK, PEEK-PEDEK, PEEK-PEoEK, and blends of two or more of said polymers; Optionally at least one plastic additive; The tape is in particular in the form of a tow prepreg or a slit tape.

32. The use according to claim 30 or 31, wherein The rotor sleeve is as described in claims 1-19.

Citation Information

Patent Citations

  • Electric machine rotor sleeve

    US20220278584A1

  • Production of aromatic polyethers

    US4176222A

  • Reinforced plastic

    US4792481A

  • Ordered polyetherketones

    US4816556A

  • Preparation of poly(arylene ether ketones)

    US4841013A